Job search is a business - Harding, Ben (Bendigo, Victoria : Video Education Australasia, 2004)
Summary: This program examines the need to be organised encourages a positive approach to the job search task. It covers setting objectives, identifying and analysing information, preparing the necessary tools and setting strategies for action.
Executive producer, Mark McAuliffe ; editor, Toby Angwin
Voice-over: Amy Blackmur
Keywords: Career; Job hunting